High vaccine effectiveness against coronavirus disease 2019 (COVID-19) and severe disease among residents and staff of long-term care facilities in Norway, November 2020-June 2021 - Jostein Starrfelt; Anders Skyrud Danielsen; Oliver Kacelnik; Anita Wang Børseth; Elina Seppälä; Hinta Meijerink (Cambridge University Press, 2022)
Coronavirus disease 2019 (COVID-19) causes high morbidity and mortality in long-term care facilities (LTCFs). COVID-19 vaccine effectiveness against infection was 81.5% and 81.4% among fully vaccinated residents and staff in LTCFs. The vaccine effectiveness against COVID-19-associated death was 93.1% among residents, and no hospitalizations occurred among fully vaccinated staff.